Enhancing Decision-Making Effectiveness through Artificial Intelligence in the Digital Office - Al Fajri, Shakira; Ailsa Videlia Rio Putri (International Journal Administration, Business & Organization, 2026)
The phenomenon of digital transformation is pivotal in redefining the operational dynamics of organizations, particularly in management and decision-making. This research examines the role of Artificial Intelligence (AI) as a strategic innovation that significantly enhances operational efficiency, precision, and analytical capabilities in digital office environments. Employing a descriptive qualitative methodology grounded in comprehensive library research, data were meticulously gathered from scholarly literature and institutional reports on the integration of AI into digital management practices. The findings reveal that AI significantly augments decision-making capabilities through heightened accuracy, efficiency, and objectivity, bolstered by Decision Support Systems, machine learning algorithms, and predictive analytics frameworks. These advanced technologies facilitate managerial identification of patterns, anticipation of trends, and the formulation of expedited, evidence-based decisions. Nonetheless, the successful implementation of these technologies requires skilled human resources, robust data governance frameworks, and an organizational culture that fosters digital innovation. Furthermore, challenges such as algorithmic bias, ethical dilemmas, and data security vulnerabilities persist as critical factors requiring careful consideration. In summary, AI is indispensable for fortifying decision-making processes and enhancing organizational competitiveness.